Optimising a help desk performance at a telecommunication company. (3rd August 2009) - AbdulMalek, Fawaz; Allahverdi, Ali
One of the problems faced by a mobile telecommunication company in Kuwait is the excessive waiting time to fix PC or software related problems of its over 800 employees. We successfully developed, validated and employed a simulation model to determine the number of technicians needed at the company to minimise total cost by considering both the cost of idle time of the employees and the wages of technicians. The simulation results indicated that the total cost can be reduced significantly by just hiring one more technician.